Regulatory mechanisms of nucleic acid-mediated innate immune responses in the tumor microenvironment - Jinushi, Masahisa (Landes Bioscience, 2012)
We identified novel mechanisms whereby TIM-3 suppresses innate immunity as induced by nucleic acids. Interaction of TIM-3 with HMGB1 inhibits the recruitment of nucleic acids to the endosomal compartment of dendritic cells, impairing the transduction of innate immune signals. Thus, TIM-3 is an effective target for enhancing the immunogenicity of nucleic acids in the context of cancer therapy.